Os desafios cotidianos no processo ensino-aprendizagem em turmas do 2º e 3º ano do Ensino Fundamental de uma escola municipal do distrito de freguesia do Andirá no município de Barreirinha – AM - Ferreira, Maicon Marinho (Brasil, 2023)
The teaching-learning process in rural schools brings with it inseparable characteristics, since education generally presents its methods, studies and practices that are different from schools in urban areas. For a quality education in the countryside, it is necessary to face and overcome many challenges, especially when it comes to riverside communities. It is important to consider its sociocultural peculiarities, which must be respected, highlighting popular practices and knowledge in the process under discussion. This research has the general objective: to analyze which are the challenges in the school routine that contribute to the difficulties in the teaching-learning process of students from classes of the 2nd and 3rd year of Elementary School in a municipal school in the District of Freguesia do Andirá, municipality of Barreirinha -AM. This is a qualitative study based on the dialectical approach that seeks to understand the research subjects and the constant movement of changes in the construction of possible debates. It is based on the assumptions of the following authors: Arroyo (1982), Borges; Oliveira (2020), Caldart (2007), Haje (2006), Lopes (2015), Martins (2020), as well as documents from Brazil (1996, 2002 and 2012). It was possible to conclude with this study that the challenges exist and that the teaching-learning process takes place in the midst of local daily life factors and that there are also structural and family situations that entail or rather negatively interfere with a more productive performance successful for our teachers and students.